Two-Hour Algorithm for Rapid Triage of Suspected Acute Myocardial Infarction Using a High-Sensitivity Cardiac Troponin I Assay. (1st November 2019) - Nestelberger, Thomas; Boeddinghaus, Jasper; Greenslade, Jaimi; Parsonage, William A; Than, Martin; Wussler, Desiree; Lopez-Ayala, Pedro; Zimmermann, Tobias; Meier, Mario; Troester, Valentina; Badertscher, Patrick; Koechlin, Luca; et al.
Abstract: BACKGROUND: We aimed to derive and externally validate a 0/2-h algorithm using the high-sensitivity cardiac troponin I (hs-cTnI)-Access assay. METHODS: We enrolled patients presenting to the emergency department with symptoms suggestive of acute myocardial infarction (AMI) in 2 prospective diagnostic studies using central adjudication. Two independent cardiologists adjudicated the final diagnosis, including all available medical information including cardiac imaging. hs-cTnI-Access concentrations were measured at presentation and after 2 h in a blinded fashion. RESULTS: AMI was the adjudicated final diagnosis in 164 of 1131 (14.5%) patients in the derivation cohort. Rule-out by the hs-cTnI-Access 0/2-h algorithm was defined as 0-h hs-cTnI-Access concentration <4 ng/L in patients with an onset of chest pain >3 h (direct rule-out) or a 0-h hs-cTnI-Access concentration <5 ng/L and an absolute change within 2 h <5 ng/L in all other patients. Derived thresholds for rule-in were a 0-h hs-cTnI-Access concentration ≥50 ng/L (direct rule-in) or an absolute change within 2 h ≥20 ng/L. In the derivation cohort, these cutoffs ruled out 55% of patients with a negative predictive value (NPV) of 99.8% (95% CI, 99.3–100) and sensitivity of 99.4% (95% CI, 96.5–99.9), and ruled in 30% of patients with a positive predictive value (PPV) of 73% (95% CI, 66.1–79). In the validation cohort, AMI was the adjudicated final diagnosis in 88 of 1280 (6.9%) patients. These cutoffs ruled out 77.9% of patients with an NPV of 99.8% (95% CI, 99.3–100) and sensitivity of 97.7% (95% CI, 92.0–99.7), and ruled in 5.8% of patients with a PPV of 77% (95% CI, 65.8–86) in the validation cohort. CONCLUSIONS: Safety and efficacy of the l hs-cTnI-Access 0/2-h algorithm for triage toward rule-out or rule-in of AMI are very high. TRIAL REGISTRATION: APACE, NCT00470587; ADAPT, ACTRN1261100106994; IMPACT, ACTRN12611000206921.